Initial performance of own-rooted and budded ’Sunraycer’ nectarine plants - Jimenes, Isabela Maria; Mayer, Newton Alex; Dias, Carlos Tadeu dos Santos; Silva, Simone Rodrigues da (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the performance in the field of 'Sunraycer' nectarine plants when own rooted and budded onto 13 clonal rootstocks. For this, flowering, flushing, fruit maturity, vigor, and production were assessed. The time span between the end of flowering and the harvest period was shorter for 'Sunraycer' budded onto the 'G x N.9', 'Santa Rosa', and 'Ishtara' rootstocks. 'Flordaguard' and 'Ishtara' induced the largest and smallest canopy sizes, respectively. 'Flordaguard' resulted in the greatest production, and 'Cadaman', in the lowest. Own-rooted 'Sunraycer' plants produce heavier fruits and can be an alternative to growers.